Pustakawan sebagai Pendidik: Analisis Kompetensi Pedagogis dan Kesiapan Instruktur dalam Literasi Informasi Akademik di Perpustakaan Universitas Riau - Thamrin Hasan; Anton Yuliarto (Jurnal Gema Pustakawan, 2026)
The transformation of the role of university libraries requires staff to transform from information curators to educators (instructional librarians). However, the lack of a pedagogical background in education presents a significant obstacle to the implementation of information literacy classes. This study aims to analyze the level of pedagogical competency knowledge and instructional readiness of staff at the University of Riau (UNRI) Library following training in teaching techniques. This quantitative descriptive study employed a total sampling approach involving 30 respondents, consisting of 20 functional librarians and 10 library technical staff. Primary data were collected through a 10-item binary objective post-test instrument based on classroom scenarios (scenario-based assessment), covering four dimensions of pedagogical competency. Data were analyzed using descriptive statistics. The results showed a mean post-test score of 66.33 (Good category), with 66.67% (20 staff) deemed to be in the safe zone of readiness to teach. Classroom management/public interaction (93.33%) and active teaching methods (83.33%) were key strengths for staff. Conversely, aspects of managing user psychology related to mitigating information anxiety/library anxiety (46.67%) and handling sudden technical teaching challenges (50.00%) were critical weaknesses experienced by staff. This study concluded that training interventions were able to improve staff's collective teaching readiness, but strengthening based on psychological empathy and mitigating digital infrastructure remains critically needed. The UNRI Library management is recommended to implement a collaborative teaching system (team teaching) between senior librarians and technical staff to standardize the quality of academic information literacy classes.